A CASE OF MANIPULATING EFL LEARNERS’ CROSS-CULTURAL UNDERSTANDING THROUGH VIDEOTAPED CONVERSATIONS AND ITS IMPACT TO SELF-REGULATED LEARNING - Yakob Metboki; Erny S. N. Hambandima (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
In the new global evolution of education, the importance of using digital media has become central issue for boosting learning effectiveness; however, less attention was weighted on its impact towards EFL learners’ learning in diversity context. This study seeks for describing learners’ cross-cultural understanding that rapidly evolves impact to learning through videotaped conversations. Sample of consisted of 13 students, taken using purposive sampling technique. The current study utilized the Motivated Strategies for Learning Questionnaire (MSLQ) developed by Pintrich et al., (1991) to point out learners’ self-regulated learning, and Mackin’s (2006) five culture dimensions to determine their cross-cultural understanding. Having projected the learners to videotape their English conversations the results show that, the process the learners jointly take out of class accounts much for extending their engagement with the content beyond class projects, enhancing their mutual integration into new groups. The projects manipulated them to construct ideas, and more surprisingly challenged them to compete for best performances in every single English conversation. Overall, the results proved that boosting the foreign learners’ learning styles to get themselves away from selfishness, shyness intensively turn into a growth beyond mutual and meaningful interactions, where there is respect for diversity on the plane of cross-cultural understanding. Keywords: Videotaped-Conversation, Cross-Cultural Understanding, Self-Regulated Learning